Effect of Different Binders on Settlement of Fibrous Peat - Kazemian, Sina (SPRINGER, 2015)
Peat commonly occurs as extremely soft, wet, unconsolidated surface deposits that are integral parts of wetland systems. The increasing growth of the population leads to the need to use peat land for development purposes. Cement is widely used for the stabilization of peat by the deep mixing method. This article describes a laboratory study on the effects of different additives on the settlement of fibrous peat. The effect of sodium silicate, ordinary Portland cement, and kaolinite on the settlement of treated peat by cementsodium silicate grout is investigated through a Rowe Cell consolidation test. At the end of this study, it is shown that increasing the amount of sodium silicate (within 2.5%), cement, and kaolinite in treated peat improves the settlement of fibrous peat much better than conventional binders like pure cement.